Estratégias genético-moleculares visando à detecção do patógeno e à identificação de análogos de genes de resistência associados com a mancha branca do milho - Ubiraci Gomes de Paula Lana (2012)
Maize is one of the most economically important cereals in the world, extensively used for food and feed, and recently, for biofuel production. Although Brazil occupies the third position on world maize production, this crop is subject to various diseases, such as white spot that has caused significant losses in production and grain quality. Despite the importance of this disease, there is a lack of information about the pathogen, which has been reported as the bacterium Pantoea ananatis, and genomicregions associated with maize white spot resistance. Thus, the main objectives of this study were: (i) to develop a diagnostic test for pathogen identification, (ii) to evaluate the genetic diversity of P. ananatis isolates, (iii) to map resistance QTL associated with white spot disease in tropical maize and (iv) to identify resistance gene analogs (RGAs) colocalized with maize white spot resistance QTL. A rapid, inexpensive and selectivediagnostic test PCR-based was implemented to detect P. ananatis. It was verified a high genetic variability among 18 isolates of the genus Pantoea from maize, sorghum, and crabgrass leaves with symptoms of the disease that should be considered in breeding programs aiming at generating resistant maize cultivars. Besides, P. ananatis from maize, sorghum and crabgrass were clustered in a single group, reinforcing theexistence of possible alternative hosts of the pathogen. Additionally, eight QTL were mapped on chromosomes 1, 2, 3, 4 and 8, accounting for approximately 90% of the genetic variance of maize white spot resistance in two environments, Sete Lagoas and Uberlândia. Data mining with 93 plant resistance genes allowed the identification of 939 RGAs in the maize genome, of which 123 were colocalized in silico with white spotresistance QTL. Among these candidate genes, Pto20, Pto99 and Xa26. 151.4 were genetically colocalized with QTL on chromosomes 4 and 8, showing an over expression pattern in the resistant line. Thus, the results generated in this study will have a fundamental contribution to design epidemiologic and genetic control strategies for maize white spot management.